A Study Of Non-Coding RNAs (ncRNAs) Of Salmonella Typhi Derived From Salmonella Pathogenicity Islands Under Different Stress Conditions - Saw, Priscilla Cheah Phei (2017)
Non-coding RNAs can be found in all bacteria including Salmonella Typhi. The Salmonella Typhi is infamous for infecting humans and causing typhoid fever, a systemic disease that may be mortal to humans. It is able to survive in various environments including in macrophags. Salmonella Typhi is similar to other bacteria by consisting of non-coding RNAs that play crucial roles in its biological pathways in response to environmental. One of the aims in this study is to investigate non-coding RNAs of Salmonella Typhi in differentiated THP-1 cells to find novel non-coding RNA expressions during invasion of macrophages via transcriptome sequencing.